2016
DOI: 10.1007/s00464-015-4713-9
|View full text |Cite
|
Sign up to set email alerts
|

Multitask training promotes automaticity of a fundamental laparoscopic skill without compromising the rate of skill learning

Abstract: BackgroundA defining characteristic of expertise is automated performance of skills, which frees attentional capacity to better cope with some common intraoperative stressors. There is a paucity of research on how best to foster automated performance by surgical trainees. This study examined the use of a multitask training approach to promote automated, robust laparoscopic skills. MethodsEighty-one medical students completed training of a fundamental laparoscopic task in either a traditional single-task traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…When attention demands increased in the multitask transfer test, errorless learners performed more accurate preparations, in terms of length/width, than errorful learners (ie the errorless group cut more conservative preparations). The errorless learning group demonstrated superior ability to perform a secondary task without diminishing performance on the primary cavity preparation task which is consistent with studies in other disciplines (eg surgery and golf) . However, the errorless approach was not associated with more accurate performance for cutting cavity depth under the multitask transfer test.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…When attention demands increased in the multitask transfer test, errorless learners performed more accurate preparations, in terms of length/width, than errorful learners (ie the errorless group cut more conservative preparations). The errorless learning group demonstrated superior ability to perform a secondary task without diminishing performance on the primary cavity preparation task which is consistent with studies in other disciplines (eg surgery and golf) . However, the errorless approach was not associated with more accurate performance for cutting cavity depth under the multitask transfer test.…”
Section: Discussionsupporting
confidence: 81%
“…For example, Masters et al found that implicit approaches to learning suturing skills in the related discipline of surgery resulted in minimal accrual of verbalisable knowledge about the skill and better performance under multitasking conditions compared to an explicit learning approach. Similar results have been found in training fundamental laparoscopic skills (ie timed peg transfer task involving picking up and transferring six objects located on pegs from left to right and then reversing the procedure); skills learned implicitly were more resilient under secondary task load than skills learned explicitly . Neuropsychological evidence also suggests that learning fundamental laparoscopic skills using implicit approaches promotes neural efficiency (ie similar to experts, reduced coactivation of the verbal‐analytic and motor planning regions was evident in implicit learning participants), by freeing up attention resources to perform concurrent tasks, as is often required by healthcare practitioners …”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Task distraction is the lack of ability to concentrate on assigned tasks (Sanders & Baron, ) and employee's attention is diverted towards non‐duty tasks and issues (Baron, ). There are different reasons behind task distraction including overburden (Patel, Zambrana, Walker, Herrmann, & Feinstein, ), lack of required skills for performing job (Poolton et al, ), stress (Nicholls, Levy, Carson, Thompson, & Perry, ), other work engagement (Horrey, Lesch, Garabet, Simmons, & Maikala, ), and SNSs addiction (Min, ). When employees spend most of their time using SNSs, their mental ability to perform job‐related tasks is reduced, which results in low level of concentration required for the assigned job.…”
Section: Introductionmentioning
confidence: 99%